2004
DOI: 10.3171/spi.2004.1.3.0243
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality intraoperative monitoring during complex lumbosacral procedures: indications, techniques, and long-term follow-up review of 61 consecutive cases

Abstract: Object. The purpose of this study was to examine the neurological outcomes after complex lumbosacral surgery in patients undergoing multimodality neurophysiological monitoring. Methods. Sixty-one patients were consecutively enrolled in this study. These patients underwent complex intra- and extradural lumbosacral procedures with concomitant intraoperative electromyography (EMG) mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 20 publications
(21 reference statements)
0
47
0
Order By: Relevance
“…65 While the advantages of neurophysiological monitoring have been demonstrated in a number of studies regarding thoracolumbar spinal lesions, data regarding its use for operations involving the cervical spine are limited. 3,31,50,65,69 Given the low incidence of new postoperative neurological deficits for surgeries in this region, SSEP inaccuracy and suboptimal sensitivity make this a poor choice for single-modality monitoring. 65,75 In fact, isolated injury to the motor tracks with sparing of the sensory pathways may allow false-negative responses and result in postoperative deficits.…”
Section: Neurophysiological Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…65 While the advantages of neurophysiological monitoring have been demonstrated in a number of studies regarding thoracolumbar spinal lesions, data regarding its use for operations involving the cervical spine are limited. 3,31,50,65,69 Given the low incidence of new postoperative neurological deficits for surgeries in this region, SSEP inaccuracy and suboptimal sensitivity make this a poor choice for single-modality monitoring. 65,75 In fact, isolated injury to the motor tracks with sparing of the sensory pathways may allow false-negative responses and result in postoperative deficits.…”
Section: Neurophysiological Monitoringmentioning
confidence: 99%
“…Additionally, EMG monitoring is also considered a very sensitive technique, but it lacks specificity. 50,65,69 Given the potentially devastating impact of a neurological injury at the cervical level, Kelleher and colleagues 65 recommended intraoperative monitoring in all operations with neurological risk despite the low incidence of neurological complications. As no single monitoring modality appears optimal alone, multimodal monitoring may be the best approach.…”
Section: Neurophysiological Monitoringmentioning
confidence: 99%
“…Ultimately, the best clinical prospect could be to combine SSEP and EMG, rather than excluding one technique from another. 11 Regarding the LFCN, one limitation lies in the fact that this nerve is purely sensory, precluding the use of usual motor nerve stimulation patterns. Nevertheless, LFCN cutaneous supply zone stimulation is possible 7,12 according to techniques published previously, 13 and recently refined.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the utility of electrophysiological monitoring in the treatment of complex lumbosacral pathological conditions. 2,3 It is possible that the relatively high number of false-negative results reported by Sansur et al reflect institutional heterogeneity in the way intraoperative electrophysiological monitoring is performed, or failure to use both electromyography and somatosensory evoked potentials to monitor the integrity of neural structures. J Neurosurg: Spine / Volume 13 / November 2010 It is clear that the surgical management of DS and IS remains challenging.…”
mentioning
confidence: 93%